Condom Use Among Men Who Have Sex With Men and Male-to-Female Transgenders in Jakarta, Indonesia. (July 2014) - Safika, Iko; Johnson, Timothy P.; Cho, Young Ik; Praptoraharjo, Ignatius
This article examined differences in condom use during anal intercourse among men who have sex with men (MSM) and male-to-female transgender women in Jakarta, Indonesia. A cross-sectional design, structured interviews, and hierarchical linear modeling were used to examine condom use among MSM recruited from entertainment places (EPs; e.g., discotheques/dance clubs/karaoke bars), massage parlors (MPs), and among transgender women who congregated and/or sought sexual partners on streets/parks (S/P). The sample consisted of 91, 97, and 114 of MSM-EP, MSM-MP, and transgender-S/P, respectively. Respondents reported on 641 unique sexual partner encounters, which were "nested" within 302 respondents. Reported condom use was high, 66%, 84%, and 83% for MSM-EP, MSM-MP, and transgender-S/P, respectively, and varied across type of respondent. At the individual level, depressive symptoms and history of physical abuse during childhood and adulthood were associated with lower condom use ( p < .05). By contrast, having a higher level of education was associated with more condom use ( p < .05). At the partner level, condom use was associated with type of partners and the use of club drugs before sex. HIV-prevention efforts should take into account the multilevel determinants of condom use within these populations.